Synthesis and Characterization of Poly-1,3-dimethyloldiacrylate propane-2-ol and Its Use as Foam - CHETRI, PRAFULLA; SEN SARMA, NEELOTPAL; NATH DASS, NARENDRA (Asian Journal of Chemistry, 2010)
Poly-1,3-dimethyloldiacrylate propane-2-ol (P-DMDAP) was prepared by the homogeneous esterification of glycerol with acrylic acid. The formation of the ester was confirmed by the IR and 1H NMR spectra. The polymer P-DMDAP shows appropriate foam character for laser target, if the density range lies 5-200 mg/cc. The pore size of the polymer was determined by SEM analysis. The thermal behaviours were studied by thermogravimetric analysis and differential thermogravimetric technique.